Deficiencies in the Legal Regulation and Judicial Practice of Kazakhstan in the Domestic Application of Treaties: entry into Force and Provisional Application - Alekbay, Zh.K. (Право и государство, № 4 (109), 2025)
The relevance of this article arises from a range of research challenges linked to the legal regulation and judicial practice of Kazakhstan in the field of domestic application of treaties. In particular, the article highlights a deficiency in the Normative Resolution of the Supreme Court of Kazakhstan «On the Application of Provisions of Treaties of the Republic of Kazakhstan» dated 10 July 2008 No. 1 (hereinafter – the 2008 Normative Resolution). Specifically, it lacks one of the legal conditions necessary for the domestic application of treaty provisions by national actors – namely, the concept of provisional application of treaties. The article also identifies judicial errors in the application of the 2004 United Nations Convention on Jurisdictional Immunities of States and Their Property – a treaty which has not entered into force for Kazakhstan and therefore holds no binding legal status within its domestic legal system. The subject of the study encompasses the legal acts of Kazakhstan governing the application of treaty provisions by national actors, as well as the provisions of the 1969 Vienna Convention on the Law of Treaties (hereinafter – the 1969 VCLT). The purpose of the research is to develop recommendations for improving legislation and judicial practice concerning the domestic application of treaties in Kazakhstan, through the analysis of relevant legal frameworks, case law, and doctrinal sources. To achieve this goal, the article employs several research methods: the case law analysis method, the formal-legal method, and the method of legal hermeneutics. The analysis of judicial practice proved useful in identifying errors made by courts when applying treaty provisions. The formal-legal method was used to assess certain provisions of the 2008 Normative Resolution for their compliance with the 1969 VCLT. Legal hermeneutics was applied to interpret the 1969 VCLT provisions using commentaries and academic doctrine. The novelty of the research lies in the results of the analysis of Kazakhstan's legislation and case law on the domestic application of treaties, specifically in terms of their compliance with the provisions of the 1969 VCLT. Based on the identified issues, the article offers the following recommendations: (a) amend the 2008 Normative Resolution by introducing a provision requiring verification of the possibility of a treaty’s provisional application as a condition for its domestic application; (b) to facilitate such verification, there is a practical need to establish a unified registry of provisionally applied treaties of Kazakhstan under the Ministry of Foreign Affairs; (c) Kazakhstani court decisions issued with reference to a non-binding treaty must be subject to reversal or revision; (d) to prevent future errors in the application of treaties, there is a need to develop a practical guide outlining the features of the domestic application of treaties that, by their nature, cannot be fully addressed through traditional legal instruments.
Keywords: Law of treaties; domestic application of treaties; conditions for domestic application of treaties; entry into force; provisional application; official publication; multilateral termination of provisional application; unilateral termination of provisional application; treaty depositary; calculation of the date of treaty entry into force